Estimasi Nilai Tambah Yang Hilang Pada Agroindustri Kakao Indonesia - Muhammad Basorudin; Banna Izzatul Hasanah; Indria Hartati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
As an agricultural country Indonesia has a lot of natural potential that can be used as export base, for example is cocoa. Unfortunately, most of the cocoa products are still exported in raw form. Even if, Indonesia also imports cocoa in the form of seeds or in processed form. As a result, there are muchlost value added of cocoa. The lost value added of cocoa is measured by the difference between processed cocoa and raw cocoa exports. The loss of added value can actually become Indonesia's revenue potential. The purpose of this research is to lose the added value of Indonesian cocoa products during the period 2009-2018. In addition, the lost value added of cocoa is also forecasted until the end of 2018. The technique used to forecast is by ARIMA method. It estimates that lost value added of cocoa every month until December 2018. The increase in lost valueadded will give benefit for Indonesianif they can undertake theirs own processing of cocoa products and publishing them to the international market in the form of processed product. Therefore, it is necessary to start to develop alternatives such as the development of production-based agro-industries, especially on the concept of cocoa, and the application of One Village One Product (OVOP) concept in order to increase cocoa productivity and minimize domestic competition.